SELAYANG PANDANG TENTANG TEOLOGI FEMINIS DAN METODE BERTEOLOGINYA - Minggus Minarto Pranoto (Sekolah Tinggi Theologia Abdiel, 2018)
The rise of women's movement and feminist theology show to us about the critical consciousness of women‟s experiences in the patriarchal society. They have fought against the patriarchal society supported by culture and religion. Many women have struggled for their self-respect, justice, and freedom. They have wanted to have an equal right and obligation with man either in church or in society. The aim of this paper is to describe the background of the rise offeminist theology and the richness of Feminist theological method.